Isomorphisim of generalized holder spaces - Rakhimov, Abdumalik A. (Institute of Physics Publishing (UK), 2013)
In this paper we prove a theorem on isomorphism of the generalized Holder’s spaces. A main result of the paper can be applied in the study of the spectral expansions in a closed domain.